2021
DOI: 10.3390/ijerph182010873
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors and Their Different Effects in Depressive Symptoms of Left-Behind Children in Rural China Compared with Non-Left-Behind Children

Abstract: In China, 61 million children were left behind in rural areas as a result of massive urbanization and migration of parents from the countryside to the cities in search of economic opportunities. This study explores the effects of environmental risk factors (i.e., peer victimization, perceived discrimination, and stressful life events) on depressive symptoms of left-behind children (LBC) and examines whether these risk factors have a higher impact on LBC compared with that of non-left-behind children (NLBC). Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Both the prevalence of depression and its temporal trend, as well as corresponding findings on access to mental health treatment, showed great geographic variances in China. These geographic variances may be caused by geography-related differences in health behaviour (like alcohol usage and physical exercise) ( 28 , 29 ), available social support and social capital (like social trust in relatives and friends, distance to the nearest medical institution, and medical assistance from non-spouse) ( 30 32 ), the prevalence of multimorbidity ( 25 ), and economic development [including average household income ( 25 , 33 ), economic welfare and social service welfare ( 34 ), and the probability of being to left-behind children ( 35 ) or empty-nest elderly ( 7 )]. In addition, as for the geographic difference in the prevalence of depression, evidence also suggested that higher altitude is more likely to be associated with symptoms of depression, with a possible mechanism that increased altitude is associated with low-pressure hypoxia, which may alter the way the brain works ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both the prevalence of depression and its temporal trend, as well as corresponding findings on access to mental health treatment, showed great geographic variances in China. These geographic variances may be caused by geography-related differences in health behaviour (like alcohol usage and physical exercise) ( 28 , 29 ), available social support and social capital (like social trust in relatives and friends, distance to the nearest medical institution, and medical assistance from non-spouse) ( 30 32 ), the prevalence of multimorbidity ( 25 ), and economic development [including average household income ( 25 , 33 ), economic welfare and social service welfare ( 34 ), and the probability of being to left-behind children ( 35 ) or empty-nest elderly ( 7 )]. In addition, as for the geographic difference in the prevalence of depression, evidence also suggested that higher altitude is more likely to be associated with symptoms of depression, with a possible mechanism that increased altitude is associated with low-pressure hypoxia, which may alter the way the brain works ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is highly desirable to identify the influencing factors and mechanisms of life satisfaction among rural LBC in order to improve their quality of life. Previous studies have shown that negative the life events could directly affect life satisfaction of LBC (Angarne-Lindberg and Wadsby, 2009;Furniss et al, 2009;Guang et al, 2017;Zhang et al, 2021). But these studies did not reveal the underlying mechanism between social support and security.…”
Section: Introductionmentioning
confidence: 88%
“…A recent study empirically demonstrated the role of core self-evaluation in mediating the relationship between negative life events and life satisfaction among college students (Junjun and Zhenzhen, 2018). However, most researches on LBC have only find that negative life events were negative related with life satisfaction (Guang et al, 2017;Zhou et al, 2020;Zhang et al, 2021). In order to explore more protective factors to reduce the impact of negative life events on the life satisfaction of left-behind children.…”
Section: Introductionmentioning
confidence: 99%
“…In China, large cities provide young adults with abundant economic resources. The migration of young parents from rural areas to large cities results in 61 million left-behind children [43], who may consequently experience emotional difficulties and develop depression or related conditions. Parental monitoring and regulation are instrumental in the prevention of Internet addiction [24].…”
Section: Migration Of Parents To Urban Areasmentioning
confidence: 99%